(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Psychosomatic disorders represent a group of conditions in which psychological, emotional, and behavioral factors play a leading role in disease onset and progression, often interacting with physiological processes. Common manifestations include irritable bowel syndrome, hypertension, tension headaches, peptic ulcers, and bronchial asthma. Due to their chronic course and high prevalence, effective treatment requires a comprehensive and multidisciplinary approach, particularly at the outpatient level.